Effect of Chemical Composition on the Structure and Catalytic Behaviour of AlPO and AlO–AlPO Mixed Catalysts - F.Sh. Mohamed; H.H. Kiwan; M.R. Mostafa (Adsorption Science & Technology, 2002)
AlPO 4 and Al 2 O 3 –AlPO 4 mixed catalysts of different composition (Al/P > 1) were prepared and calcined in the temperature range 350–650°C. Such catalysts were characterized by DTA and X-ray diffraction methods, and by nitrogen adsorption studies at −196°C. Their acidity was determined using a calorimetric titration method while their catalytic activity towards the dehydration of isopropanol was determined using a pulse microcatalytic technique. The data obtained from XRD studies showed that pure AlPO 4 when calcined at 650°C had a rather low crystallinity with its crystalline structure (which is of the α-cristobalite type) being characterized by poorly developed peaks. However, significant changes in the texture, surface acidity and catalytic activity were observed as a result of changing the chemical composition of the solid, with the surface area, total pore volume and surface acidity generally increasing with increasing alumina content. Sintering commenced above 550°C leading to a decrease in the surface area and to pore widening. Dehydration of isopropanol appeared to be insensitive to the structure of the catalysts investigated but was related to the surface acid density.